2012
DOI: 10.3892/ijo.2012.1522
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of dipeptidyl peptidase 8 and 9 in breast and ovarian carcinoma cell lines

Abstract: Abstract. Proteases, particularly serine proteases like dipeptidyl peptidase 4 (DP4) and fibroblast activation protein (FAP), play an important role in cancer invasion and angiogenesis. Aberrant expression of DP4 and FAP is associated with numerous cancers, including breast and epithelial ovarian carcinoma. We investigated the mRNA levels, protein expression and enzyme activity of the structural homologs DP8 and DP9, in addition to DP4 and FAP, in three breast carcinoma (MDA-MB-231, MDA-MB-453, MCF-7), three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Thus, by means of their associations and substrate specificities, the DPP4/FAP heteromeric complex is responsible for tumour invasion, migration, metastasis and angiogenesis [6,7,13,[22][23][24]. Furthermore, potential roles of DPP8 and DPP9 have been suggested in breast and ovarian cancer and an upregulation of DPP9 has been detected in testicular tumours [35,94,132]. In addition, DPP9 was found to regulate cell survival and proliferation by inhibiting Akt activation involving the EGF signalling pathway.…”
Section: Role Of Dash Proteins In Diseasesmentioning
confidence: 99%
“…Thus, by means of their associations and substrate specificities, the DPP4/FAP heteromeric complex is responsible for tumour invasion, migration, metastasis and angiogenesis [6,7,13,[22][23][24]. Furthermore, potential roles of DPP8 and DPP9 have been suggested in breast and ovarian cancer and an upregulation of DPP9 has been detected in testicular tumours [35,94,132]. In addition, DPP9 was found to regulate cell survival and proliferation by inhibiting Akt activation involving the EGF signalling pathway.…”
Section: Role Of Dash Proteins In Diseasesmentioning
confidence: 99%
“…DPP8 mRNA expression is significantly greater than all the other DPPs in breast cancer and ovarian cancer cell lines, but DPP8 and DPP9 protein expression is ubiquitous across those cell lines (70). DPP9 mRNA is also greatly upregulated in human testicular tumors (59).…”
Section: Dpp8 and Dpp9 In Cell Behavior And Tumor Biologymentioning
confidence: 99%
“…DPP9 mRNA is also greatly upregulated in human testicular tumors (59). Interestingly, the highest level of DPP9 protein is in 2 estrogen receptor negative breast cancer cell lines that are negative for DPPIV mRNA (70). In many tumor tissues, including skin melanotic melanoma, neuroblastoma, and leukemia, the long form of human DPP9 mRNA is expressed (23).…”
Section: Dpp8 and Dpp9 In Cell Behavior And Tumor Biologymentioning
confidence: 99%
“…In cancer, increased DP8 mRNA has been found in chronic lymphocytic leukemia (12) and DP9 mRNA in testicular cancer (3), and increased levels of DP8/DP9 mRNA, protein, and enzymatic activity have been observed in human meningiomas (13). Ubiquitous but differential expression of DP8/DP9 has been observed in breast and ovarian carcinoma cell lines (14), and a study has identified DP8/DP9 as survival factors for the Ewing sarcoma family of tumors (15). Despite these findings, the mechanism(s) of DP8/DP9 function in these events has yet to be identified, and their exact biological roles remain unknown.…”
Section: Introductionmentioning
confidence: 99%